A Randomized, Dose-Finding, Proof-of-Concept Study of Berberine Ursodeoxycholate in Patients With Primary Sclerosing Cholangitis. (22nd November 2022) - Kowdley, Kris V.; Forman, Lisa; Eksteen, Bertus; Gunn, Nadege; Sundaram, Vinay; Landis, Charles; Harrison, Stephen A.; Levy, Cynthia; Liberman, Alexander; Di Bisceglie, Adrian M.; Hirschfield, Gideon M.
Abstract : INTRODUCTION: Primary sclerosing cholangitis (PSC) is a fibroinflammatory disease of the bile ducts leading to cirrhosis and hepatic decompensation. There are no approved pharmaceutical therapies for PSC. Berberine ursodeoxycholate (HTD1801) is an ionic salt of berberine and ursodeoxycholic acid with pleiotropic mechanisms of action. METHODS: An 18-week proof-of-concept study was conducted to assess the safety and efficacy of HTD1801 in PSC. This study had three 6-week periods: (i) a placebo-controlled period, (ii) a treatment extension period, and (iii) a randomized treatment withdrawal period. The primary end point was change from baseline in alkaline phosphatase (ALP) at week 6. RESULTS: Fifty-five patients were randomized and treated; 35 (64%) had inflammatory bowel disease and 22 (40%) had previously received ursodeoxycholic acid. Patients were initially randomized to placebo (n = 16), HTD1801 500 mg BID (n = 15), or HTD1801 1000 mg BID (n = 24). At baseline, mean (range) ALP values were 414 U/L (138–1, 048), 397 U/L (237–773), and 335 U/L (122–882) for the placebo, HTD1801 500 mg BID, and HTD1801 1, 000 mg BID groups, respectively. At week 6, a significant decrease in ALP was observed with HTD1801 (least square mean; HTD1801 500 mg BID = −53 U/L, P = 0.016; HTD1801 1000 mg BID = −37 U/L, P = 0.019) compared with placebo (98 U/L). ALP reductions were sustained through week 18 in those who remained on therapy, whereas ALP increased in those who crossed over to placebo during period 3. HTD1801 was generally well tolerated; 4 patients experienced serious adverse events, none attributed to HTD1801. DISCUSSION: HTD1801 is associated with significant improvement in ALP and warrants further study as a treatment for PSC.